2022
DOI: 10.1101/2022.03.23.485457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial phosphoproteomes are functionally specialized across tissues

Abstract: Mitochondria are essential organelles involved in critical biological processes such as energy metabolism and cell survival. Their dysfunction is linked to numerous human pathologies that often manifest in a tissue-specific manner. Accordingly, mitochondrial fitness depends on versatile proteomes specialized to meet diverse tissue-specific requirements. Furthermore, increasing evidence suggests that phosphorylation may also play an important role in regulating tissue-specific mitochondrial functions and pathop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 138 publications
(147 reference statements)
2
7
0
Order By: Relevance
“…6H ). We observed the same phenotype in mitochondria isolated from the brain of MCUB KO mice, where we and others (Samaras et al , 2020; Hansen et al , 2024) could detect a clear expression of MCUB ( Fig. S6A-C ).…”
Section: Resultssupporting
confidence: 84%
“…6H ). We observed the same phenotype in mitochondria isolated from the brain of MCUB KO mice, where we and others (Samaras et al , 2020; Hansen et al , 2024) could detect a clear expression of MCUB ( Fig. S6A-C ).…”
Section: Resultssupporting
confidence: 84%
“…Given that the spleen accommodates a huge quantity of immune cells (predominantly B cells and T cells), our observation indicated the elevated mitochondrial biogenesis and dynamics within this organ that might be required by immune cell development and migration 39 . Cross-analysis with the reported indepth tissue proteomic data 40 , showed that our captured "kidneyonly" and "spleen-only" proteomes were typically more significant in the reported dataset for the corresponding tissue (Supplementary Fig. 17), further supporting the proteomic characteristics observed by CAT-S.…”
Section: Cat-s Enabled Mitochondrial Proteome Profiling For Primary C...supporting
confidence: 73%
“…For comparison and validation, the proteins detected only in postcutoff kidney and spleen proteomes (i.e., "kidney-only" and "spleenonly") were cross-analyzed with the published datasets 40 (https://www. ebi.ac.uk/pride/archive/projects/PXD030062) of high-coverage mitochondrial proteomics for mouse tissues by Mann group, which contained six samples for each tissue.…”
Section: Mitochondrial Proteomic Profiling For Living Tissuesmentioning
confidence: 99%
“…J.K.P and K.K. were supported by a Mito Foundation Incubator Grant (2022) and Mito Foundation Ph.D. scholarship, respectively. We would like to thank Kathy Krentz and C. Dustin Rubenstein from the Animal Models and Genome Editing Cores at the University of Wisconsin-Madison for generating of the Pptc7 floxed model.…”
Section: Acknowledgementsmentioning
confidence: 99%